Insufficiency of the Customs Union as an Engine of Economic Development in the Northern Triangle of Central America [Недостатки Таможенного Союза Как Двигателя Экономического Развития В Северном Треугольнике Центральной Америки] [Insuficiencia de la Unión Aduanera Como Motor de Desarrollo Económico en el Triángulo Norte Centroamericano] - Gomez-Del Cid, R (Institute of Latin American Studies, Russian Academy of Sciences, 2020)
The Customs Union (UA) of the Northern Triangle of Central America (TNC) of entered into force on November 20, 2018, based on the Protocol on inclusion in the process of deep integration between Guatemala and Honduras after the accession of El Salvador. The academic debate of the article revolves around the central objective: Why is the Customs Union insufficient in the TNC countries? This is due to auxiliary elements such as theoretical exclusivity, the absence of a Single External Tariff, and the inability to fully apply it in the participating countries. The results show that the current evolution of the UA does not meet the original goals, because it is limited to facilitating intraregional trade and does not perceive the UA as an opportunity to increase the possibilities of economic development through industrialization, which is currently insufficient. © 2020. All rights reserved.